Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.23
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Dimensional Gender Bias Classification

Abstract: Machine learning models are trained to find patterns in data. NLP models can inadvertently learn socially undesirable patterns when training on gender biased text. In this work, we propose a novel, general framework that decomposes gender bias in text along several pragmatic and semantic dimensions: bias from the gender of the person being spoken about, bias from the gender of the person being spoken to, and bias from the gender of the speaker. Using this fine-grained framework, we automatically annotate eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 75 publications
1
58
0
Order By: Relevance
“…Liu et al also proposes two methods for debiasing, one of which we also employ (i.e., CDA), and the other of which extends to sentences a word-embedding post-processing method (Bolukbasi et al, 2016) that has been shown to be ineffective at removing gender bias (Gonen and Goldberg 2019, but see for a more recent, perhaps more effective attempt). Finally-and as a direct extension of this work- Dinan et al (2020) decomposes gender bias along three semantic-pragmatic dimensions, and show that train more fine-grained classifiers allow for more accurate classification of dataset gender biases. The novelty of the present contribution lies in how we measure bias, and in the joint application of our three gender debiasing methods.…”
Section: Related Workmentioning
confidence: 80%
See 1 more Smart Citation
“…Liu et al also proposes two methods for debiasing, one of which we also employ (i.e., CDA), and the other of which extends to sentences a word-embedding post-processing method (Bolukbasi et al, 2016) that has been shown to be ineffective at removing gender bias (Gonen and Goldberg 2019, but see for a more recent, perhaps more effective attempt). Finally-and as a direct extension of this work- Dinan et al (2020) decomposes gender bias along three semantic-pragmatic dimensions, and show that train more fine-grained classifiers allow for more accurate classification of dataset gender biases. The novelty of the present contribution lies in how we measure bias, and in the joint application of our three gender debiasing methods.…”
Section: Related Workmentioning
confidence: 80%
“…Nouns and adjectives are binned into gendered bins via an aggregation of existing gendered word lists (Zhao et al, 2018b,a;Hoyle et al, 2019). Note that other functions could be used as well, such as a bias classifier (Dinan et al, 2020).…”
Section: Bias Controlled Trainingmentioning
confidence: 99%
“…Bias metrics can also be categorized by how they define associations between demographic group attributes and text. Biases can be towards people described in text, people who produce the text, or people to whom the text is addressed (Dinan et al, 2020b). Most existing works define bias metrics through the first association-these biases are relatively easier to analyze, since both the demographic and the textual signals of bias are encapsulated within the text.…”
Section: Bias Definitions and Metricsmentioning
confidence: 99%
“…They applied logit pairing to improve CTF and assured robust accuracy for similar sentences targeting different demographics. In another work, Dinan et al (2020) decomposed gender bias in text along several pragmatic and semantic dimensions and proposed classifiers for controlling gender bias.…”
Section: Bias In System Outputmentioning
confidence: 99%